Who Am I? Reflecting on a Personal Journey of Self-Authorship - Vaughn, Laura (Journal of International Students, 2023)
This reflective paper shares the experiences of a higher education professional living and working abroad and the long-term impacts of those experiences on their self-authorship journey through reflection ten years later. The story of this reflection focuses on how cultural differences and community ties helped to facilitate growth and self-confidence through navigating the challenges and complexities of living abroad in a culture with differing conventions. The paper concludes by sharing how reflecting on self-authorship during and after international experiences can help develop personal identities both as an individual and within a collective.